KEKUATAN ALAT BUKTI PETUNJUK MEMPENGARUHI KEYAKINAN DALAM PUTUSAN HAKIM PADA PROSES PEMBUKTIAN PERKARA PIDANA - Telaumbanua, Yoses Ondrasi; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
This article discusses the influence of the strength of indicative evidence on the judge's confidence in the process of proving criminal cases. This research uses normative research methods, namely legal research carried out by analyzing library materials or secondary data. In this context, research highlights how the strength of indicative evidence can influence judges' beliefs. Indicative evidence refers to actions, events, or circumstances that show a connection either between these elements or with the criminal act itself, indicating that a criminal act has occurred and identifying the perpetrator. This article also briefly discusses the murder case involving the defendant Jessica Wongso and the deceased victim Mirna. This case is taken as an example to evaluate the strength of indicative evidence, with a focus on the use of electronic evidence such as CCTV in trials. Through this research, it is hoped that it can be better understood how the strength of indicative evidence plays an important role in shaping judges' beliefs during the evidentiary process in criminal cases, by exploring the use of electronic evidence in the context of specific cases.Keywords: Guidance Evidence, Judge's Confidence, Judge's Decision